PROBLEMS OF MODELING ON THE SUBJECT "DRAWING GEOMETRY AND ENGINEERING GRAPHICS" - Ziyovuddin Safarovich Khojamov (Scholar Express Journal, 2021)
This scientific article discusses the problems of modernization of curricula for teaching the subject "Descriptive Geometry and Engineering Graphics". There are opinions and comments on the algorithms created for the curricula of specialties on the implementation of the program.
Keywords: Modernization; technology; resource; complex